2016
DOI: 10.1080/2055074x.2016.1198545
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of alkylation of benzene with ethanol over bimetallic modified HZSM-5 zeolite catalyst and effects of percentage metal loading

Abstract: According to International Zeolite Association (2014), until now, there are 218 zeolite framework type codes that have been discovered. Worldwide consumption of zeolites (natural and synthetic) is estimated to be about 5 million tons per year. The annual market for synthetic zeolites and molecular sieves was developed vastly to 1,800,000 ton worldwide in 2008. 3 Alkylation of benzene is a vital reaction in the petrochemical industry. Benzene alkylation technologies offer improvements in octane number and gasol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The result from the NH 3 ‐TPD is supported by a comprehensive analysis of X‐ray diffraction (XRD), low‐angle X‐ray diffraction (LAXRD), N 2 sorption investigation, and chemical titration (Table S1). The Beta‐0.1 N NaOH specimen displays a remarkable mesoporous surface area (S meso =158 m 2 g −1 ) and a diverse distribution of acid sites, that are primarily accountable for the alkylation reactions [69] . After the base treatment the catalytic efficiency of material is enhanced, which is represented by increase in the peak for the strong acid sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result from the NH 3 ‐TPD is supported by a comprehensive analysis of X‐ray diffraction (XRD), low‐angle X‐ray diffraction (LAXRD), N 2 sorption investigation, and chemical titration (Table S1). The Beta‐0.1 N NaOH specimen displays a remarkable mesoporous surface area (S meso =158 m 2 g −1 ) and a diverse distribution of acid sites, that are primarily accountable for the alkylation reactions [69] . After the base treatment the catalytic efficiency of material is enhanced, which is represented by increase in the peak for the strong acid sites.…”
Section: Resultsmentioning
confidence: 99%
“…The Beta-0.1 N NaOH specimen displays a remarkable mesoporous surface area (S meso = 158 m 2 g À 1 ) and a diverse distribution of acid sites, that are primarily accountable for the alkylation reactions. [69] After the base treatment the catalytic efficiency of material is enhanced, which is represented by increase in the peak for the strong acid sites. The low-temperature peak is indicative of desorption of ammonia from Lewis acid sites with weak acidity, whereas the high-temperature peak is correlated with Brönsted acid sites that exhibit greater acidity.…”
Section: Catalystmentioning
confidence: 99%
“…Subsequently, an ethoxy cation attacks benzene molecule to form protonated ethylbenzene. Ethylbenzene is eventually obtained when a protonated ethylbenzene returns a proton to the zeolite surface . In order to avoid the production of diethylbenzene and higher hydrocarbons via the secondary reactions, we fixed the ratio of benzene to ethanol at 2:1.…”
Section: Results and Discusssionmentioning
confidence: 99%
“…Ethylbenzene is eventually obtained when a protonated ethylbenzene returns a proton to the zeolite surface. 70 In order to avoid the production of diethylbenzene and higher hydrocarbons via the secondary reactions, we fixed the ratio of benzene to ethanol at 2:1. It was reported that with a lower volume fraction of benzene, there is a higher possibility of diethylbenzene formation due to a higher alkylation activity of ethylbenzene caused by the positive inductive effect of ethyl group and eventually the catalyst can be easily deactivated.…”
Section: Catalytic Activity Testingmentioning
confidence: 99%